Horror films of the 1990s - Muir, John Kenneth, 1969- (McFarland & Co., Inc., 2011)
"This detailed filmography surveys more than 300 horror films that were released in the years 1990 through 1999. The horror genre's trends, clichés and patterns of the decade are connected to social and cultural phenomena. Among the popular forms of this period were serial killers, aliens, conspiracies, and "interlopers," new monsters who wreak havoc"--Provided by publisher.